1996
DOI: 10.1113/jphysiol.1996.sp021333
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential difference and intracellular cation concentrations in human placental trophoblast cells in culture.

Abstract: 1. The electrochemical gradients for Na+ and K+ were assessed in a cell culture model of trophoblast differentiation. 7. The Nae equilibrium potential (ENa) was positive in the trophoblast cells and the difference between ENa and Em was 122, 100 and 100 mV in JAr, mono-and multinucleate cytotrophoblast cells, respectively.8. These results suggest that the electrochemical gradient for K' is affected by the stage of trophoblast cell differentiation. In contrast, the electrochemical gradient for Na+ is similar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…Na + -linked co-transport). With the use of microelectrodes, a fetal-side negative potential difference has been shown to exist across the human syncytiotrophoblast/cytotrophoblast layer (Greenwood et al, 1993a;Greenwood et al, 1996). The microvillous membrane potential (E m ) is significantly more negative (hyperpolarized) in first trimester villi compared to term (Birdsey et al, 1997).…”
Section: Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na + -linked co-transport). With the use of microelectrodes, a fetal-side negative potential difference has been shown to exist across the human syncytiotrophoblast/cytotrophoblast layer (Greenwood et al, 1993a;Greenwood et al, 1996). The microvillous membrane potential (E m ) is significantly more negative (hyperpolarized) in first trimester villi compared to term (Birdsey et al, 1997).…”
Section: Potassium Channelsmentioning
confidence: 99%
“…2F). The Na + pump actively extrudes sodium from the cell in exchange for K + using energy in the form of ATP (Clarson et al, 1996). This generates an inwardly directed Na + gradient which in turn facilitates the Na + entry mechanisms.…”
Section: Na + /K + /Atpasementioning
confidence: 99%
“…Cytotrophoblast cells were isolated using an adaptation of the method of Kliman et al (30) as previously described in detail (7,18). Briefly, human placentas were collected within 30 min of delivery, and the villous tissue was removed, roughly minced, and washed thoroughly with saline.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…All cells were maintained at 37°C in a humidified incubator gassed with 5% CO 2-95% air for up to 3 days of culture. We have previously shown that during this time cytotrophoblast cells isolated from human term placenta undergo both morphological and biochemical differentiation to form multinuclear syncytiotrophoblast-like cells (7,18). Cells were studied at two time points in culture: after 18 h, when the majority of cells are mononuclear, and after 66 h, when the majority of cells are multinucleate syncytiotrophoblast-like cells.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation